Research portfolio - Kruger, H J M (Rhodes University, Faculty of Education, Department of Education, 2004)
Paper 1. The purpose of this analysis is to critically evaluate the Lower Primary Mathematics programme within the context of the Namibian educational reform, against the backdrop of learner-centred education from within the Constructivist epistemology. Through the analysis of a small-scale survey, I will try to determine the extent to which learners, teachers and other educationalists, involved in the Lower Primary school phase, understand the new approach to Mathematics and their pedagogical and theoretical insight into the new programme. I will also analyse the syllabus documents in view of the educational policies and further discuss the social, historical and economic background to the reform. I will then analyse the progress or development of the reform process through discussing the learning environment as well as the learners who are the central participants in education. Paper 2.This critical discussion aims to explore the prospects and underlying principles of the epistemologies of two opposing paradigms of education: Behaviourism and Constructivism. I have critically examined and compared the theoretical aspects that shape and inform the model of instruction and the systemic implications of the learning process. The purpose was to compare both learning theories and to draw a conclusion of which the better epistemology is for the teaching and learning process. Paper 3. This is an investigation into the theories that underpin and inform mathematics teaching in the Lower Primary phase of the primary school in Namibia. The Namibian society requires the development of knowledge and understanding, skills and competencies, attitudes and values, which everyone must have to be able to function adequately in society on a social, economic and political level (MBESC 1996). We need to seek ways of enhancing mathematics teaching in Namibia if we want to live up to the expectations of our society. Paper 4. Mathematicians and researchers across the globe have theorised and speculated about education reform movements, which aim for more than just structural knowledge where it concerns Mathematics. This action research study is based on the findings of a pilot study about 'Problem-based Learning', using this as a basis to investigate the relationship between the intentions of the Lower Primary Mathematics curriculum and its implementation at classroom level. This paper reports on a case study of two grade one teachers' perceptions of problem solving as a key component of Mathematics learning and how the implementation of the problem-based approach could be supported through intervention. Data was gathered from a series of cycles of planning, acting, observing and reflecting. Analysis of the data indicates that teachers' professional development lies within a willingness to change and in reflexive practice. Given focused support to teachers could result in the application of contemporary approaches to Mathematics teaching, with an overall improvement of constructivist-oriented learner-centred education.
Keywords: Mathematics -- Study and teaching (Elementary) -- Namibia; Problem solving -- Study and teaching (Elementary) -- Namibia